Correction: Tetrafluorinated phenylpyridine based heteroleptic iridium(iii) complexes for efficient sky blue phosphorescent organic light-emitting diodes. Issue 21 (27th May 2020) - Chen, Zhao; Suramitr, Songwut; Zhu, Nianyong; Ho, Cheuk-Lam; Hannongbua, Supa; Chen, Shuming; Wong, Wai-Yeung
Abstract : Correction for 'Tetrafluorinated phenylpyridine based heteroleptic iridium(iii ) complexes for efficient sky blue phosphorescent organic light-emitting diodes' by Zhao Chen et al., J. Mater. Chem. C, 2020, 8, 2551–2557, DOI: ; 10.1039/C9TC05779J .